2022
DOI: 10.1186/s12905-022-02063-8
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of the fecal microbiome with the biochemical profile during menopause: a Brazilian cohort study

Abstract: Background Hormonal, biochemical, and metabolic changes after menopause may alter the quality of life of women, leading to vasomotor, psychological, and genitourinary symptoms, and changes in their gut microbiota, which regulates estrogen levels through the estroboloma. Fecal samples were used to investigate the changes in the gut microbiota during aging and hormonal changes in women. A balanced gut microbiota has been associated with health or disease conditions and remains poorly understood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
0
1
Order By: Relevance
“…In this study, the positive effect of Lactobacillus on bone density was also mentioned. 35 In our study, however, no relationship was found between the relative abundance of Lactobacillus and serum calcium. This result may be partly because our female participants were postmenopausal.…”
Section: Discussioncontrasting
confidence: 77%
“…In this study, the positive effect of Lactobacillus on bone density was also mentioned. 35 In our study, however, no relationship was found between the relative abundance of Lactobacillus and serum calcium. This result may be partly because our female participants were postmenopausal.…”
Section: Discussioncontrasting
confidence: 77%